Bioremediation of shrimp pond wastewater using effective microorganism-4 (EM4) - Annisa Maysabila; Rika Heryanti; Rega Permana; Zahidah Hasan (Aceh Journal of Animal Science, 2023)
The problems of shrimp farming with semi-intensive systems are leftover feed, organic matter, and toxic compounds that can reduce water quality. Shrimp pond wastewater treatment can be done through several technologies, such as bioremediation. Bioremediation is a biological process that utilizes microorganisms to decompose waste in aquaculture ponds into compounds that are not harmful to aquatic biota. This research aims to determine the effect of effective microorganism-4 (EM4) in reducing ammonia compounds and BOD levels in shrimp pond wastewater. The research method used is a laboratory-scale experimental method. A total of 9 aquariums were used for 3 different treatments with two replications, control, adding EM4 2.5% and EM4 3% to 5 liters of wastewater. The water quality parameters observed were dissolved oxygen, temperature, pH, ammonia, and BOD. Data analysis used is one way ANOVA test. The results showed that there was a decrease in ammonia and BOD levels. The highest reduction of ammonia was found in the treatment with the addition of EM4 2.5%, while the decrease in BOD with the highest effectiveness was found in the control treatment (37.73%) with the initial BOD value 5.3 to 3.3. mg/l . In conclusion, the small dosage addition of EM4 did not have a significant effect on decreasing levels of ammonia and BOD.